Odpowiedzi

2010-03-25T14:03:22+01:00
2x+1=4x+5
2x-4x=5-1
-2x=4
x=-2

5-x=x+3
-x-x=3-5
-2x=-2
x=1

-3x+4=8-x
-3x+x=8-4
-2x=4
x=-2

2x-4=5x+2
2x-5x=2+4
-3x=6
x=-2

x-1=5-x
x+x=5+1
2x=6
x=3

2+1x=9-5x
x+5x=9-2
6x=7
x=7/6
x=1 1/6
2010-03-25T14:04:12+01:00
2x+1 = 4x+5
2x-4x = 5-1
-2x = 4 |:(-2)
x = -2

5-x = x+3
-x-x = 3-5
-2x = -2 |:(-2)
x = 1

-3x+4 = 8-x
-3x+x = 8-4
-2x = 4 |:(-2)
x = -2

2x-4 = 5x+2
2x-5x = 2+4
-3x = 6 |:(-3)
x = -2

x-1 = 5-x
x+x = 5+1
2x = 6 |:2
x = 3

2+x = 9-5x
x+5x = 9-2
6x = 7 |:6
x = 1i1/6
2010-03-25T14:20:08+01:00
2x + 1 =4x + 5
2x - 4x =5-1
-2x=4/÷(-2)
x=-2

5-x=x+3
-x-x=3-5
-2x=-2/÷(-2)
x=1

-3x+4=8-x
-3x+x=8-4
-2x=4/÷(-2)
x=-2

2x-4=5x+2
2x-5x=2+4
-3x=6/÷(-3)
x=-2

x-1=5-x
x+x=5+1
2x=6/÷2
x=3

2+1x=9-5x
1x+5x=9-2
6x=7/÷6
x=⁷/₆=1¹/₆